Tribological behavior of graphene-based friction composite tested on cryogenically treated cast iron. (September 2022) - Ravikumar, N; Tamilarasan, TR; Rajendran, R; Pragatheeswaran, R
Enhancement of friction and wear performance is the basic requirement of a friction composite material, which primarily relies on the properties of ingredients and the type of counter disc. To meet the superior requirements of the tribological system, a new tribopair between graphene-based friction composite and cryogenic treated grey cast iron disc was designed in this work. Friction composites in the shape of a pin were made from solid lubricants—20 wt.% of molybdenum disulfide, 20 wt.% of graphite, and 10 wt.%, 15 wt.%, and 20 wt.% of graphene nanopowder. The prepared five friction composites are tested on the cryogenic treated grey cast iron disc and untreated disc in a pin-on-disc tribometer under dry state conditions, resulting in 10 different tribopairs. The tribological efficacy of the tribopairs was assessed and finally compared with the tribopair formed from a commercial brake pad. Results proved that the tribological performance of the tribopairs, namely 20 wt. % of graphene nanopowder—cryogenic treated grey cast iron disc and 15 wt.% of graphene nanopowder—cryogenic treated grey cast iron disc was superior compared to the other tribopairs. Thus, the addition of graphene nanopowder in the friction composite and cryogenic treatment of the grey cast iron disc significantly affects the overall friction and wear properties of the tribopairs. Scanning electron microscopy micrographs were used to characterize the friction composites surface and counter disc.